An Ambazonian theology? A theological approach to the Anglophone crisis in Cameroon - Morris-Chapman, Daniel Pratt (HTS teologiese studies, 2019)
The last 3 years have witnessed a period of substantial volatility in Cameroon. In 2016, protests within the minority Anglophone regions against the obligatory use of French in schools triggered a period of considerable unrest, in which hundreds of people have been incarcerated and killed. Following an increased security presence in the English-speaking regions, armed groups have surfaced calling for secession – the creation of an independent nation of Ambazonia. In view of this escalating crisis, this article will investigate how the ‘Anglophone problem’ in Cameroon might be brought to bear upon the African theological debate by examining issues of violence, marginalisation and fragmentation within the two English-speaking areas of Cameroon.